Isolation and characterization of antioxidant polysaccharides (PKCP-D70-2-a and PKCP-D70-2-b) from the Pinus koraiensis pinecone. Issue 112 (21st November 2016) - Zhang, Hua; Zhao, Haitian; Zhou, Xintao; Yang, Xin; Shen, Siyan; Wang, Jing; Wang, Zhenyu; Geng, Lin
Abstract : Water-soluble polysaccharides from Pinus koraiensis pinecone was fractionated using DEAE cellulose-52 and Sephadex G-100 successively to obtain two eluents named PKCP-D70 -2-a and PKCP-D70 -2-b. Abstract : Water-soluble polysaccharides from Pinus koraiensis pinecone were fractionated using DEAE cellulose-52 and Sephadex G-100 successively to obtain two eluents named PKCP-D70 -2-a and PKCP-D70 -2-b. Structural analyses showed that PKCP-D70 -2-a had a higher molecular weight and degree of branching when compared to PKCP-D70 -2-b. Structural analyses also showed that the monosaccharide composition of PKCP-D70 -2-a differed from that of PKCP-D70 -2-b. The existence of a O -glycopeptide bond in PKCP-D70 -2-a and PKCP-D70 -2-b was verified by a β-elimination reaction. Tertiary structure analyses indicated that PKCP-D70 -2-a and PKCP-D70 -2-b had a triple-helical conformation. However, PKCP-D70 -2-b had more of a triple-helical conformation when compared to PKCP-D70 -2-a. PKCP-D70 -2-a and PKCP-D70 -2-b showed stronger radical scavenging capacities. The results also signified that polysaccharides from Pinus koraiensis pinecone could be investigated as potential antioxidant agents for complementary medicine and for functional foods.